Four-Corner Arthrodesis versus Proximal Row Carpectomy: Risk Factors and Complications Associated with Prolonged Postoperative Opioid Use - Li, Neill Y.; Kuczmarski, Alexander S.; Hresko, Andrew M.; Goodman, Avi D.; Gil, Joseph A.; Daniels, Alan H. (Journal of Hand and Microsurgery, 2020)
Introduction This article compares opioid use patterns following four-corner arthrodesis (FCA) and proximal row carpectomy (PRC) and identifies risk factors and complications associated with prolonged opioid consumption.Materials and Methods The PearlDiver Research Program was used to identify patients undergoing primary FCA (Current Procedural Terminology [CPT] codes 25820, 25825) or PRC (CPT 25215) from 2007 to 2017. Patient demographics, comorbidities, perioperative opioid use, and postoperative complications were assessed. Opioids were identified through generic drug codes while complications were defined by International Classification of Diseases, Ninth and Tenth Revisions, Clinical Modification codes. Multivariable logistic regressions were performed with p < 0.05 considered statistically significant.Results A total of 888 patients underwent FCA and 835 underwent PRC. Three months postoperatively, more FCA patients (18.0%) continued to use opioids than PRC patients (14.7%) (p = 0.033). Preoperative opioid use was the strongest risk factor for prolonged opioid use for both FCA (odds ratio [OR]: 4.91; p < 0.001) and PRC (OR: 6.33; p < 0.001). Prolonged opioid use was associated with an increased risk of implant complications (OR: 4.96; p < 0.001) and conversion to total wrist arthrodesis (OR: 3.55; p < 0.001) following FCA.Conclusion Prolonged postoperative opioid use is more frequent in patients undergoing FCA than PRC. Understanding the prevalence, risk factors, and complications associated with prolonged postoperative opioid use after these procedures may help physicians counsel patients and implement opioid minimization strategies preoperatively.
Keywords: proximal row carpectomy; four-corner arthrodesis; prolonged opioid use; complications; total wrist arthrodesis